2018
DOI: 10.3389/fimmu.2018.02660
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Specificity and Clinical Significance of IgG and IgA Autoantibodies Produced in situ by Tumor-Infiltrating B Cells in Breast Cancer

Abstract: An important role for tumor infiltrating B lymphocytes (TIL-B) in the immune response to cancer is emerging; however, very little is known about the antigen specificity of antibodies produced in situ. The presence of IgA antibodies in the tumor microenvironment has been noted although their biological functions and clinical significance are unknown. This study used a 91-antigen microarray to examine the IgG and IgA autoantibody repertoires in breast cancer (BC). Tumor and adjacent breast tissue supernatants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 47 publications
(57 reference statements)
3
51
0
Order By: Relevance
“…TIL-B are functional, reflected by their production of autoantibodies specific for TAA, with a previous demonstration that BC TIL-B expand oligoclonally (74). Our recent analysis of paired primary tissue supernatant and plasma samples detected autoantibodies in > 84% of our BC cohort to 1 or more antigens on a 91-TAA microarray (39). The 3 most frequently recognized proteins were ankyrin repeat domain 30B like (ANKRD-30BL), COP9 signalosome subunit 4 (COPS4), and CTAG1B (also known as NY-ESO-1).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…TIL-B are functional, reflected by their production of autoantibodies specific for TAA, with a previous demonstration that BC TIL-B expand oligoclonally (74). Our recent analysis of paired primary tissue supernatant and plasma samples detected autoantibodies in > 84% of our BC cohort to 1 or more antigens on a 91-TAA microarray (39). The 3 most frequently recognized proteins were ankyrin repeat domain 30B like (ANKRD-30BL), COP9 signalosome subunit 4 (COPS4), and CTAG1B (also known as NY-ESO-1).…”
Section: Discussionsupporting
confidence: 77%
“…The 3 most frequently recognized proteins were ankyrin repeat domain 30B like (ANKRD-30BL), COP9 signalosome subunit 4 (COPS4), and CTAG1B (also known as NY-ESO-1). This work also found that higher IgG but not IgA responses to BC-associated antigens were associated with shorter recurrence-free survival and lower CD8 + TIL, suggesting that Ig isotypes may provide different biological functions in the tumor microenvironment (39). In the present study, global Ig production -and specifically IgG1 levels -increase in the tumor tissue supernatant as TIL levels graduate from low to intermediate to high, but this was also associated with a bump in IgA in the TIL int group.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Plasma cells in tumor tissue expressed IgGs rather than IgAs that were detected in paired normal tissue. IgGs have been associated with a pro-cancer role by influencing myeloid cell Fc-receptors (48).…”
Section: Discussionmentioning
confidence: 99%